Identification of QTL for Plant Height Traits in Single-segment Substitution Lines of Wild Rice - Xingxin DAI; Yanjie LIU; Chengxia LI; Rui TANG; Jiamei MU; Xuelin FU (Guangdong nongye kexue)
【Objective】Plant height is an agronomic trait closely related to rice plant architecture, which has an important role in the formation of rice yield. Through fully exploring the elite genetic loci for plant height in wild rice, it would be helpful in the enrichment of dwarf genes and to provide new genetic resources for breeding rice varieties with ideal plant height.【Methods】In the study, two sets of single-segment substitution lines, MER-SSSLs from Oryza meridionalis and BARSSSLs from O. barthii, were used as donor parents, and the phenotypes of plant height were investigated through multi-season field trials. To detect QTLs controlling plant height in SSSLs, the different significance between the SSSLs and the recipient parent 'HJX74' were analyzed by Duncan's multiple comparison test.【Results】The plant heights of the MER-SSSLs and BAR-SSSLs showed a unimodal distribution in all three seasons with a wide variation range, and the ranges were from 80.74 cm to 116.22 cm and 80.26 cm to 167.33 cm, respectively. A total of 25 QTLs related to plant height were identified in MERSSSLs, the additive effects of the QTLs ranged from -6.07 cm to 6.35 cm, and the phenotype variation explained by individual QTL was from 2.34% to 6.63%. Among them, seven QTLs (qPHm2-1, qPHm2-2, qPHm3-1, qPHm4-2, qPHm5-1, qPHm5-4, and qPHm5-5) were identified repeatedly in different seasons, presenting as stable QTLs. Importantly, qPHm2-1, qPHm2-2, qPHm3-1, qPHm4-2, and qPHm5-4 have not been reported previously, which were considered novel QTLs controlling plant height traits in MER-SSSLs from O. meridionalis. In BAR-SSSLs, a total of 21 QTLs were identified in late season of 2024, the additive effects ranged from -5.41 cm to 29.28 cm, with the phenotype contributions ranging from 2.45% to 30.13%. Both qPHb1-4 and qPHb10-1 showed the phenotype contributions of more than 18.00%, and qPHb10-1 might be a novel QTL controlling plant height traits in BAR-SSSLs from O. barthii.【Conclusion】Plant height is a quantitative trait controlled by multiple genes in rice. Seven stable QTLs for plant height in SSSLs of O. meridionalis and two main QTLs in SSSLs of O. barthii were identified. It lays a foundation for further cloning of the elite genes for plant height in wild rice, and provides valuable genetic resources for breeding rice varieties with ideal plant height.